South American Fomitiporia (Hymenochaetaceae, Basidiomycota) 'jump on' exotic living trees revealed by multi-gene phylogenetic analysis - Morera, Guillermo (2017)
Morphological and molecular analyses of Fomitiporia neotropica specimens occurring in different native and exotic tree hosts were performed. For molecular analyses we used three markers (LSU, ITS and tef1-α). The molecular analyses revealed the existence of two morphologically similar species. One of them, Fomitiporia impercepta sp. nov., is described here. The phylogenetic position of these species reveals a South American origin and their occurrence on exotic living tree species hints at their capabilities of new host jump events in evolution. These species do not share same hosts suggesting they are not completely generalist wood-decay fungi.